Second Five Year Plan Bombay State Surat District - Government of Bombay (Government of Bombay, 1950)
The Second Five-Year Plan (1956–61) for Surat District, Bombay State, outlines a comprehensive strategy for socio-economic development encompassing agriculture, irrigation, industry, transport, education, health, housing, and welfare for marginalized communities. The plan builds on achievements from the First Five-Year Plan to implement a sequential and integrated development framework aimed at improving the quality of life and economic resilience of the district’s population. Agricultural initiatives focus on enhancing productivity through the distribution of improved seeds, modern implements, and training in advanced farming practices, while major irrigation schemes, including the Kakarapara Weir and the Ukai Multipurpose Project, aim to expand irrigated areas and ensure water security for agriculture, with hydropower generation as a supplementary benefit. Economic diversification is pursued through the promotion of cottage and industrial cooperatives, handloom development, and fisheries infrastructure, coupled with training and mechanization programs to increase employment and income opportunities. Transport and communication improvements, particularly road network expansion and the enhancement of public transport under the Bombay State Road Transport Corporation, are designed to facilitate trade, market access, and connectivity. Educational initiatives prioritize compulsory primary education, expansion of secondary schools, and grants for higher education institutions, with vocational and technical courses to meet the evolving needs of the district’s economy. Public health measures focus on establishing hospitals, dispensaries, mobile medical units, and disease control programs for malaria and filaria, while housing initiatives target industrial workers and low-income groups through cooperative housing schemes and the construction of 28,000 subsidized tenements. Welfare programs for backward classes emphasize education, scholarships, vocational training, economic support, and social inclusion, complemented by legislative measures to reduce social inequalities. Community participation and cooperative engagement are central to the plan’s success, ensuring localized decision-making and effective resource utilization. Overall, the Second Five-Year Plan for Surat District represents a holistic and multi-sectoral approach to sustainable regional development, aiming to strengthen agricultural productivity, industrial growth, social welfare, and infrastructure, while fostering inclusive growth for all sections of the population.
Surat District
Surat District
Keywords: State Plan; Surat District Development; Agricultural Productivity; Irrigation Projects; Cottage and Industrial Cooperatives; Road and Transport Infrastructure; Public Health Initiatives; Educational Expansion; Housing Programs; Backward Classes Welfare; Fisheries and Rural Development; Community Participation